PENGARUH PENAMBAHAN GEL LIDAH BUAYA (ALOE VERA) PADA PEMBUATAN SKIN LOTION DARI MINYAK KELAPA MURNI (VIRGIN COCONUT OIL) - Endo Pebri Dani Putra; Rendy Rayhka Pratama (AGROINTEK, 2022)
This research was aimed to determine the effect of addition of aloe vera gel toward characteristic of skin lotion and to determine the best addition of aloe vera gel. This research used a completely randomized design (CRD) consisiting of 5 treatments and 3 replications. Data were analyzed statistically using ANOVA followed by Duncan’s New Multiple Range Test (DNMRT) at 5% significance level. Treatment in the present research is the addition of aloe vera gel at 0 g;  5 g; 10 g; 15 g; and 20 g. The observations to the result of skin lotion product were organoleptic, physical analysis, chemical analysis, product moisturize test, irritation test, microbiological analysis and antioxidant activity test. The physical analysis which is observed such as viscosity, specific gravity, emulsion stability and chemical analysis which is observed such as pH value. The result of this research showed that the difference in addition of aloe vera gel to skin lotion significantly affected to specific gravity, moisture activities of product, pH and antioxidant activity and did not significantly affected to viscosity and emulsion stability. The best products based on organoleptic test on skin lotion was treatment B (addition of aloe vera gel 5 g), with an average of panelists score to appearance 87%, color 83%, aroma 70%, thick consistency 77% and stickiness 87%, while the result physical and chemical analysis skin lotion of treatment B (addition of aloe vera gel 5 g) is viscosity 8.333 cP; specific gravity 1,01; emulsion stability 100%; product moisture 98,07%; pH value 7,771; antioxidant activity 16,60%; irritation value 0; and total plate count 9,5 x 101 cfu/ml.